Evaluation of relationship between orthodontic treatment need according Dental Aesthetic Index (DAI) and student’s perception in 11-14 year old students in the city of Shiraz in 2012 - Danaee, Shahla Momeni; Fijan, Soleiman; Mohammadi, Najmeh; Zadeh, Rojin Soleiman (International Journal of Research in Medical Sciences, 2017)
Background: Although the demand for orthodontic treatment is affected by understanding the needs for treatment and costs, patients’ concerns do not always match with expert’s assessments. To gain a clearer understanding of children’s orthodontic needs, treatment recommendations and how an abnormality can affect a child’s quality of life is critical. Information on the relationship between assessment of need for treatment and an individual’s perception of need for orthodontic treatment is of great interest for orthodontic service providers. The present study aimed to assess the relationship between need for orthodontic treatment according to Dental Aesthetic Index (DAI) and individuals’ perception of need for treatment in 11-14 year old students. Methods: In this study, 240 primary and middle school students from the four educational districts of Shiraz were selected through multi-stage random sampling and completed the study questionnaire. Then dental examination was done by the dentist according to DAI index to determine the student’s need for orthodontic treatment. Results: According to the results, 73.8% of the students had DAI score of13-25 (little or no need for treatment), 15.2% had DAI score of 25-30 (specific malocclusion with elective need for treatment), 4.4% had DAI score of 30-35 (severe malocclusion with extreme need for treatment), and 6.7% had DAI score exceeding 35 indicating their serious need for orthodontic treatment. The total mean score of DAI was 23.57. Conclusion: The results revealed a significant relationship between the students’ perception of need for treatment and professional assessment of need for orthodontic treatment based on DAI index (P = 0.002).